2017
DOI: 10.3389/fimmu.2017.00960
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Single-Domain Antibody Fragments That Preferentially Detect Intact (146S) Particles of Foot-and-Mouth Disease Virus for Use in Vaccine Quality Control

Abstract: Intact (146S) foot-and-mouth disease virus (FMDVs) can dissociate into specific (12S) viral capsid degradation products. FMD vaccines normally consist of inactivated virions. Vaccine quality is dependent on 146S virus particles rather than 12S particles. We earlier isolated two llama single-domain antibody fragments (VHHs) that specifically recognize 146S particles of FMDV strain O1 Manisa and shown their potential use in quality control of FMD vaccines during manufacturing. These 146S-specific VHHs were speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 49 publications
(69 reference statements)
0
31
0
Order By: Relevance
“…Five protomers, each of which consists of one set of structural proteins (VP1, VP2, VP3, and VP4), assemble to form a pentamer, and 12 copies of the pentamer and the encapsidated viral RNA form a 146S particle [ 3 ]. Intact virus particles, followed by empty capsids (75S) are known to confer the most potent protective immunity to vaccinated animals compared to pentamers (12S) that are poor at conferring immune protection [ 4 ]; however, 146S can easily dissociate into less immunogenic 12S particles by weak acid or mild heat [ 4 , 5 ]. Therefore, stabilization of 146S particles is a key technique for FMD vaccine production.…”
Section: Introductionmentioning
confidence: 99%
“…Five protomers, each of which consists of one set of structural proteins (VP1, VP2, VP3, and VP4), assemble to form a pentamer, and 12 copies of the pentamer and the encapsidated viral RNA form a 146S particle [ 3 ]. Intact virus particles, followed by empty capsids (75S) are known to confer the most potent protective immunity to vaccinated animals compared to pentamers (12S) that are poor at conferring immune protection [ 4 ]; however, 146S can easily dissociate into less immunogenic 12S particles by weak acid or mild heat [ 4 , 5 ]. Therefore, stabilization of 146S particles is a key technique for FMD vaccine production.…”
Section: Introductionmentioning
confidence: 99%
“…To corroborate the thermofluor data generated using the mutated SAT2/O viruses we used an ELISA-based technique which uses a single-domain llama antibody (M377F VHH) that specifically recognises intact FMDV capsid (146S) 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Doel and Baccarini showed that live viruses of types A and C are more stable than types O and SAT1-3, with SAT viruses being particularly sensitive to temperature 8 . To determine the thermostability of the viruses used in this study two recently reported techniques were used, (i) thermofluor analysis (also termed PaSTRy: Particle STability using Release assaY) which monitors genome release as a consequence of capsid dissociation and (ii) ELISA using a llama single-domain antibody that recognises intact FMDV particles (146S infectious virions or 75S VLPs) 15 , 16 , 18 , 23 , 24 . In these assays purified virus samples were used to standardise experimental conditions and to ensure samples predominantly consisted of 146S intact virions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations